Prevalence and characterization of antimicrobial-resistant Escherichia coli isolated from veterinary staff, pets, and pet owners in Thailand - Shutipen Buranasinsup; Anuwat Wiratsudakul; Boonrat Chantong; Khuanwalai Maklon; Sarin Suwanpakdee; Sineenard Jiemtaweeboon; Walasinee Sakcamduang (Elsevier, 2023)
Background: Companion animals may act as antimicrobial resistance (AMR) reservoirs. This study investigated the prevalence and AMR patterns of Escherichia coli in pets and people in close contact with pets. Methods: A total of 955 samples were collected from veterinary clinics across Thailand by rectal and skin or ear swabs from dogs and cats and fecal swabs from veterinarians, veterinary assistants, and pet owners. The minimum inhibitory concentrations (MICs) of the obtained isolates were investigated using Sensititre™ MIC plates against 21 different antimicrobial drugs. Results: Escherichia coli from pets was frequently resistant to ampicillin (100%) and amoxicillin-clavulanic acid (100%), whereas E. coli from pet owners, veterinarians, and veterinary assistants was mostly resistant to tetracycline. The multiple antibiotic resistance index revealed that multidrug-resistant E. coli isolates were frequently found in dogs (34.92%), cats (62.12%), veterinarians (61.11%), veterinarian assistants (36.36%), and pet owners (47.62%). The most common AMR genes identified in this study were blaCTX-M, blaTEM, tetA, and tetB, which were associated with the antimicrobial susceptibility results. Additionally, extended-spectrum beta-lactamase (ESBL)-associated genes (i.e., blaCTX-M, blaTEM, and blaSHV) were found in 21.69%, 71.97%, 27.78%, and 21.43% of E. coli isolated from dogs, cats, veterinarians, and pet owners, respectively. Conclusions: Our findings demonstrated the presence of AMR genes, particularly ESBL-associated genes, in E. coli isolated from healthy pets and veterinarians. This implies that these sources of E. coli could potentially be reservoirs for antibiotic resistance, thereby increasing the risk of harm to both humans and animals. These findings highlight the importance of implementing effective AMR control measures in veterinary practices, as bacteria resistant to commonly used antimicrobials are present in humans and animals.